Targeting Neutrophils in Sepsis: From Mechanism to Translation - Shen, Xiaofei; Cao, Ke; Zhao, Yang; Du, Junfeng (Frontiers in Pharmacology, 2021)
Sepsis is a life-threatening condition caused by a dysregulated host response to infection. Although our understanding in the pathophysiological features of sepsis has increased significantly during the past decades, there is still a lack of specific treatment for sepsis. Neutrophils are important regulators against invading pathogens, and their role during sepsis has been studied extensively. It has been suggested that the migration, antimicrobial activity and the function of neutrophil extracellular traps (NETs) have all been impaired during sepsis, which result in an inappropriate response to primary infection and potentially increase the susceptibility to secondary infection. On the other hand, accumulating evidence has shown that the reverse or restore of neutrophil function can promote bacterial clearance and improve sepsis outcome, supporting the idea that targeting neutrophils may be a promising strategy for sepsis treatment. In this review, we will give an overview of the role of neutrophils during sepsis and discuss the potential therapeutic strategy that targets on neutrophils.